Identifying and Addressing Genetic Counseling Challenges among Indigenous People of Oaxaca—One Center's Experience with Two Immigrant Farmworker Families in the Central Valley of California. Issue 4 (3rd February 2018) - Shen, Joseph J.; Carmichael, Jason; Vásquez Santos, Leoncio
Abstract: An important aspect of genetic counseling is the recognition of and adaptation to the socio‐cultural uniqueness of the different populations that a genetics clinic serves. The Central Valley of California is home to a large population from Mexico, with a significant proportion of indigenous ancestry originating from the state of Oaxaca. We report on our experience with two families of this community—one extended family with an early lethal inborn error of metabolism and the other with a chronic disfiguring form of ichthyosis. We identified multiple important factors that needed to be considered, including the matching of language dialects, adaptation to different social interaction conventions, acknowledgement of traditional medicine beliefs, and effective transmission of genetic terms and concepts, all of which should be incorporated into the interactions with these families when aiming to provide comprehensive genetic counseling.